Efficiency of ovine artificial insemination in Ouled Djellal breed - Allaoui A.; Safsaf B.; Djaalab I.; Laghrour W.; Haffaf S.; Tlidjane M. (Technology creation and transfer in small ruminants: roles of research, development services and farmer associations, 2014)
In Algeria the artificial insemination is a common application in cattle and is at its beginnings in sheep. To assess the impact of this biotechnology on the control of reproduction in Ouled Djellal breed (OD), we conducted a study at the artificial insemination and genetic amelioration center (CNIAAG) in Biskra’s department and at Bouchebaa’s model farm in Constantine’s Department. Our study focused on 350 ewes OD aged from 2 to 6 years and divided into two groups: (A) 300 ewes maintained at the farm Bouchebaa, rely on free mating, and (B) 50 ewes maintained at the CNIAAG – Biskra. Zootechnical performances are lower in group B (fecundity rate = 101% vs 66%, fertility rates = 86.70% vs 64% and prolificacy rate = 116,54% vs 103%, respectively for free mating vs AI); for the last two parameters, this difference was significant (p <0.02). Concerning the success factors of AI, the statistical analysis revealed no significant difference for the age (9 months, 3, 4 or 6) or class (yearling or adult) ram used for the semen harvest. In conclusion we can say that the success rate of AI will never be similar to natural reproduction. So that farmers continue to show a limited interest for this technique. It should be noted that to date, the success rate recorded at AI sheep centers in Algeria vary from 46 to 76%. However in free mating it is almost impossible to determine the paternal ancestry of newborns.
8. Seminar of the FAO-CIHEAM Sub-Network on Production Systems, 2013/06/11-13, Tangier (Morocco)